PENERAPAN ACTIVE KNOWLADGE SHARING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMAN 2 SOPPENG - Rahmatullah, Sity; Bunyamin, Andi; Syahrul, Muhammad; Raehana, Syarifah; Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to improve Islamic Education (PAI) learning outcomes for grade XI.9 students at SMA Negeri 2 Soppeng through the implementation of the Active Knowledge Sharing method. The primary issue addressed is the low level of student engagement and learning achievement caused by conventional teaching methods. This study utilizes Classroom Action Research (CAR) consisting of planning, acting, observing, and reflecting stages. The subjects were students of class XI.9 at SMA Negeri 2 Soppeng. Data were collected through observation sheets of student activities and learning outcome tests. The results indicate that the application of the Active Knowledge Sharing method effectively enhances student participation and comprehension of PAI materials. This improvement is evidenced by the increase in average test scores and the percentage of students achieving the minimum mastery criteria across cycles. In conclusion, the Active Knowledge Sharing method is an effective strategy for improving the quality of PAI learning at SMA Negeri 2 Soppeng. It is recommended that teachers adopt this method as an innovative, student-centered alternative to foster collaborative learning. Keywords: Active Knowladge Sharing, Learning Outcomes, Islamic Education